2017
DOI: 10.1155/2017/1521407
|View full text |Cite
|
Sign up to set email alerts
|

Primary Occipital Ewing’s Sarcoma with Subsequent Spinal Seeding

Abstract: Ewing's sarcoma is a primary bone cancer that mainly affects the long bones. This malignancy is particularly common in pediatric patients. Primary cranial involvement accounts for 1% of cases, with occipital involvement considered extremely rare. In this case study, primary occipital Ewing's sarcoma with a posterior fossa mass and subsequent relapse resulting in spinal seeding is reported. A 3-year-old patient presented with a 1-year history of left-sided headaches, localized over the occipital bone with progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Although primary intracranial extraosseous ES with leptomeningeal dissemination has been rarely described in the literature, no other cases share the extent of central nervous system metastasis present in this patient. [5][6][7] Radiation and chemotherapeutic management strategies for primary intracranial ES with metastasis are illustrated in Table 1. [5][6][7][8][9] A study of 14 cases from a single institution revealed that patients who underwent adjuvant radiotherapy had statistically significant improvement in 1-and 2-year survival and median survival time compared to patients without radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although primary intracranial extraosseous ES with leptomeningeal dissemination has been rarely described in the literature, no other cases share the extent of central nervous system metastasis present in this patient. [5][6][7] Radiation and chemotherapeutic management strategies for primary intracranial ES with metastasis are illustrated in Table 1. [5][6][7][8][9] A study of 14 cases from a single institution revealed that patients who underwent adjuvant radiotherapy had statistically significant improvement in 1-and 2-year survival and median survival time compared to patients without radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Radiation and chemotherapeutic management strategies for primary intracranial ES with metastasis are illustrated in Table 1. [5][6][7][8][9] A study of 14 cases from a single institution revealed that patients who underwent adjuvant radiotherapy had statistically significant improvement in 1-and 2-year survival and median survival time compared to patients without radiotherapy. 6,10 Radiation regimens are typically initiated postoperatively with the standard craniospinal irradiation protocol of 36 Gy in 21 fractions followed by a boost to 54 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptom at presentation was headache and emesis (10/12, 83.3%). 2,3,6,7,[9][10][11][12][13][14][15] Extracranial spread was uncommon, occurring in only two patients. Management typically requires a multimodal approach to include resection, radiotherapy, and intensive multiagent chemotherapy.…”
Section: Ewing Sarcomamentioning
confidence: 97%